(untitled) (Research, Society and Development, 2022)
The Brazilian northeastern semi-arid is a region composed of countless microorganisms adapted to extreme conditions, and to ensure their survival, they can produce several biomolecules and develop peculiar mechanisms. The use of microorganisms has been reported as a promising alternative for promoting plant growth through the production of several bioactive molecules, which can replace chemical agents that cause environmental problems. In this study, Bacillus sp. Ar 16 (UFPEDA), isolated from the rhizosphere of Aroeira (Schinus terebinthifolia) from the Caatinga biome, northeastern semi-arid region, was taxonomically characterized through biochemical tests, Matrix-Assisted Laser Desorption Ionization Time of Flight Mass Spectrometry (MALDI-TOF) and 16S region rRNA such as Bacillus cereus UFPEDA 1060 B (99.86%). In vitro conditions, the B. cereus UFPEDA 1060B strain produced exopolysaccharide (EPS), cellulases, and phosphatases and presented maximum phosphate solubilization of 880 µg.mL -1 . Furthermore, the production of 3.96 to 4.06 µg.mL -1 of indole acetic acid (IAA) in a culture medium supplemented with 5 mM of L-tryptophan was evidenced. IAA and other organic acids were extracted and analyzed by High-Performance Liquid Chromatography (HPLC) at a retention time of 6.2. The studied strain has different mechanisms that can promote plant growth and is also capable of controlling the growth of Fusarium spp. and Colletotrichum spp. The effectiveness of the results presented by this strain demonstrate its biotechnological potential, which can bring benefits to sustainable agriculture with artifices that favor, in addition to plant growth, the cycling of nutrients.